2022
DOI: 10.3390/languages7030181
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assessment of Word Learning to Diagnose Developmental Language Disorder in French-Speaking Monolingual and Bilingual Children

Abstract: Dynamic assessment (DA), which evaluates the learning process rather than static knowledge, has been found to be effective in diagnosing developmental language disorder (DLD) in English-speaking bilingual children. We present three studies that examine whether a French dynamic word learning task can distinguish caseload children with DLD from control children with typical development (TD). Forty-eight monolingual and 69 bilingual French-speaking children, aged four to nine, were required to learn three to six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Numerous studies have evaluated word learning using a DA approach (40,(63)(64)(65)(66)(67)(68)(69)(70)(71). Kapantzoglou et al (40) assessed twentyeight Spanish-English bilingual children with low SES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have evaluated word learning using a DA approach (40,(63)(64)(65)(66)(67)(68)(69)(70)(71). Kapantzoglou et al (40) assessed twentyeight Spanish-English bilingual children with low SES.…”
Section: Introductionmentioning
confidence: 99%
“…As for French-speaking children, Matrat et al ( 71 ) recently reported on three studies that used a word-learning task based on Kapantzoglou et al ( 40 ) and Hasson et al ( 65 ). In the first study, they found that bilinguals with TD performed less well than monolinguals on static measures of vocabulary knowledge but not on dynamic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Les résultats détaillés peuvent être consultés dans l'article princeps (Matrat et al, 2022) qui est en libre accès. Ainsi, le lecteur intéressé pourra prendre connaissance des analyses et des résultats statistiques exhaustifs, résultats que nous résumons ci-dessous.…”
Section: Résultatsunclassified
“…Contrastingly, other studies indicate that bilingual TD children also show difficulties in this task [50]. Moreover, consecutive bilingual children seem to perform worse than both monolinguals and simultaneous bilingual children in fast mapping tasks [42]. Kan and Kohnert [51] point to bilingual children's learning potential for such tasks in their L1 (first or family language) being higher than in their L2 (second or societal language).…”
Section: Introductionmentioning
confidence: 98%
“…When neither knowledge of both languages of the child nor computerised solutions are available, static vocabulary tasks in only one of the languages spoken appear to be insufficient compared to Dynamic Assessment (DA, [42]), which is considered an appropriate and feasible diagnostic tool for DLD in bilingual children [43,44]. DA targets children's language learning potential for the acquisition of new words, applying "test-teach-retest" procedures [45] and systematically providing and recording feedback [46].…”
Section: Introductionmentioning
confidence: 99%